The Urgency and Efforts to Improve Financial Literacy in Early Childhood Education: A Literature Review - Permatasari, Anggraeni Dian; Iftitah, Khofifa Najma (Universitas Muhammadiyah Surakarta, 2023)
Financial literacy is a fundamental literacy skill that is very important to have. As with other basic literacy, financial literacy is very important to instil in early childhood. However, the literature review that focuses on financial literacy in early childhood still needs to be improved. This research aims to analyze the urgency of financial literacy and the efforts that can be made to teach financial literacy in Early Childhood Education. The method used in this research is a literature review adapted from Chigbu et al. (2023). Based on the results of the review, it was found that financial literacy is very important to develop in early childhood because it is a critical period in children's brain development and the rapid development of executive functions. Efforts that can be used to foster financial literacy from an early age include providing knowledge about the concept of money, the concept of needs and desires, the concept of saving, and sharing with others. These efforts can be made through picture storybooks, interactive media, role-play using artificial money, and interactive games. Financial literacy learning in early childhood can use Project Based Learning (PjBL) and learning cycle learning methods. The review resulting from this research can be a basis for future researchers to develop research related to understanding financial literacy in early childhood. Apart from that, this article can also provide knowledge for stakeholders to develop financial literacy learning at the PAUD level.